2000
DOI: 10.1161/01.res.87.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Production of 20-HETE and Its Role in Autoregulation of Cerebral Blood Flow

Abstract: In the brain, pressure-induced myogenic constriction of cerebral arteriolar muscle contributes to autoregulation of cerebral blood flow (CBF). This study examined the role of 20-HETE in autoregulation of CBF in anesthetized rats. The expression of P-450 4A protein and mRNA was localized in isolated cerebral arteriolar muscle of rat by immunocytochemistry and in situ hybridization. The results of reverse transcriptase-polymerase chain reaction studies revealed that rat cerebral microvessels express cytochrome P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
273
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 285 publications
(290 citation statements)
references
References 22 publications
14
273
3
Order By: Relevance
“…This finding is consistent with previous work demonstrating that PG is released from glial cells (22,23), and that 20-HETE synthesis occurs downstream at the level of vascular smooth muscle cells (24). These results also clarify why we did not previously observe a PG component of neurovascular coupling in the ex vivo retina (6); that earlier ex vivo study was conducted entirely in 95% O 2 , effectively suppressing the PG component of the response.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with previous work demonstrating that PG is released from glial cells (22,23), and that 20-HETE synthesis occurs downstream at the level of vascular smooth muscle cells (24). These results also clarify why we did not previously observe a PG component of neurovascular coupling in the ex vivo retina (6); that earlier ex vivo study was conducted entirely in 95% O 2 , effectively suppressing the PG component of the response.…”
Section: Discussionsupporting
confidence: 92%
“…20-Hydroxyeicosatetraenoic acid (20-HETE) is one of the AA metabolites produced by some CYP isozymes, which we termed 20-HETE synthase, mainly by CYP4A and 4F (Laethem et al, 1992;Roman, 2002). It has been reported that 20-HETE acts as a potent vasoconstrictor of cerebral microvessels (Harder et al, 1994), and has an important role in the autoregulation of cerebral blood flow (Gebremedhin et al, 2000). 20-Hydroxyeicosatetraenoic acid has also been reported to induce the formation of oxygen radicals by interacting with nicotinamide adenine dinucleotide phosphate-oxidase and nitric oxide synthase (Wang et al, 2006;Cheng et al, 2008;Medhora et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, 20-HETE is a potent constrictor of cerebral arteries (Gebremedhin et al, 1998(Gebremedhin et al, , 2000, and the levels of 20-HETE increase in CSF following SAH (Kehl et al, 2002;CambjSapunar et al, 2003). Inhibition of the synthesis of 20-HETE, with 17-octadecynoic acid (17-ODYA) or HET0016, or blockade of its vasoconstrictor actions with WIT0002 prevents the acute fall in cerebral flow following SAH (Kehl et al, 2002;Yu et al, 2004).…”
mentioning
confidence: 99%